A digital information ecosystem structure for regional climate change assessment and adaptation - Hussain, Omar; Perdomo, Antuaned; Dillon, Tharam S.; Chang, Elizabeth (IEEE, 2009)
Global warming is one of the most important and challenging problems being faced in the current century. It triggers along with it a series of events that will have serious consequences on the different ecosystems on planet earth. In order to avoid and manage such consequences, we need dedicatedactions for resilience. In such a scenario the process of adaptation to climate change plays an important part. This is achieved by first identifying the various events of risks, assessing the level of their impacts and then developing policies by which they can be mitigated. For effective adaptation, theevents of global warming should be identified and assessed on a regional scale. In this paper, we propose a digital information ecosystem architecture for climate change adaptability. The proposed architecture will capture the different regional factors of global warming and then link them together formaking effective macro adaptation policies.